2017 Progress in Electromagnetics Research Symposium - Spring (PIERS) 2017
DOI: 10.1109/piers.2017.8262295
|View full text |Cite
|
Sign up to set email alerts
|

Chaotic communication with robust hyperbolic transmitter and receiver

Abstract: New chaos-based communication schemes for transmission of analog and digital information are suggested. The carrier signal is produced by chaotic generator having well-defined oscillation phases at least on short time intervals. For data extraction, a special procedure of phase detection for chaotic signals is developed. An efficiency of the scheme is demonstrated by examples of coupled generators of structurally stable (robust) chaos with hyperbolic attractors of Smale-Williams and Arnold's "cat map" types. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
3
0
1
Order By: Relevance
“…As control parameters adopted by the parameters a and c, let us design the synergetic observer by setting parameter b as "known" [13,[26][27][28][29]. According to overall design procedure [40], we replace the unknown parameters with their dynamic models .…”
Section: Two-channel Synergetic Observer Analytical Design Procedures mentioning
confidence: 99%
See 2 more Smart Citations
“…As control parameters adopted by the parameters a and c, let us design the synergetic observer by setting parameter b as "known" [13,[26][27][28][29]. According to overall design procedure [40], we replace the unknown parameters with their dynamic models .…”
Section: Two-channel Synergetic Observer Analytical Design Procedures mentioning
confidence: 99%
“…In addition, we note that using only MCM is a more secure approach due to nonlinear mixing of the useful signal and MCM as a secure scheme is thus widely used in much research as indicated below. Different approaches and applications of chaotic data communication systems design have been illustrated in several recent papers [23][24][25][26]. Examples of CSK and DCSK were presented by Yang et al [23] and Cheng et al [24].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Для повышения надежности в [4][5][6] предлагается использовать генераторы с хаотическими аттракторами гиперболиче-ского типа. А сохранение конфиденциальности передаваемой инфор-мации напрямую связано со сложностью используемых хаотических колебаний.…”
Section: возбуждение хаотических и квазипериодических колебаний 47unclassified